Nickel‐Based Metal–Organic Frameworks for Coal‐Bed Methane Purification with Record CH4/N2 Selectivity. (18th February 2022) - Wang, Shao‐Min; Shivanna, Mohana; Yang, Qing‐Yuan
Abstract: The enrichment and purification of coal‐bed methane provides a source of energy and helps offset global warming. In this work, we demonstrate a strategy involving the regulation of the pore size and pore chemistry to promote the separation of CH4 /N2 mixtures in four nickel‐based coordination networks, named Ni(ina)2, Ni(3‐ain)2, Ni(2‐ain)2, and Ni(pba)2, (where ina =isonicotinic acid, 3‐ain =3‐aminoisonicotinic acid, 2‐ain =2‐aminoisonicotinic acid, and pba =4‐(4‐pyridyl)benzoic acid). Among them, Ni(ina)2 and Ni(3‐ain)2 can effectively separate CH4 from N2 with top‐performing performance because of the suitable pore size (≈0.6 and 0.5 nm) and pore environment. Explicitly, Ni(ina)2 exhibits the highest ever reported CH4 /N2 selectivity of 15.8 and excellent CH4 uptake (40.8 cm 3  g −1 ) at ambient conditions, thus setting new benchmarks for all reported MOFs and traditional adsorbents. The exceptional CH4 /N2 separation performance of Ni(ina)2 is confirmed by dynamic breakthrough experiments. Under different CH4 /N2 ratios, Ni(ina)2 selectively extracts methane from the gaseous blend and produces a high purity of CH4 (99 %). Theoretical calculations and CH4 ‐loading single‐crystal structure analysis provide critical insight into the adsorption/separation mechanism. Ni(ina)2 and Ni(3‐ain)2 can form rich intermolecular interactions with methane, indicating a strong adsorption affinity between pore walls and CH4 molecules. Importantly, Ni(ina)2 has good thermal and moisture stability and can easily be scaled up at a low cost ($25 per kilogram), which will be valuable for potential industrial applications. Overall, this work provides a powerful approach for the selective adsorption of CH4 from coal‐bed methane. Abstract : A family of nickel‐based coordination networks with different pore environments was synthesized. These porous materials could be used for coal‐bed methane purification with exceptional separation performance.